Advancements and Prospects in Perovskite Solar Cells: From Hybrid to All-Inorganic Materials - Fernando Velcic Maziviero; Dulce M. A. Melo; Rodolfo L. B. A. Medeiros; Ângelo A. S. Oliveira; Heloísa P. Macedo; Renata M. Braga; Edisson Morgado (Nanomaterials, 2024)
Hybrid perovskites, materials composed of metals and organic substances in their structure, have emerged as potential materials for the new generation of photovoltaic cells due to a unique combination of optical, excitonic and electrical properties. Inspired by sensitization techniques on TiO2 substrates (DSSC), CH3NH3PbBr3 and CH3NH3PbI3 perovskites were studied as a light-absorbing layer as well as an electron–hole pair generator. Photovoltaic cells based on per-ovskites have electron and hole transport layers (ETL and HTL, respectively), separated by an ac-tive layer composed of perovskite itself. Major advances subsequently came in the preparation methods of these devices and the development of different architectures, which resulted in an efficiency exceeding 23% in less than 10 years. Problems with stability are the main barrier to the large-scale production of hybrid perovskites. Partially or fully inorganic perovskites appear promising to circumvent the instability problem, among which the black perovskite phase CsPbI3 (α-CsPbI3) can be highlighted. In more advanced studies, a partial or total substitution of Pb by Ge, Sn, Sb, Bi, Cu or Ti is proposed to mitigate potential toxicity problems and maintain device efficiency.